2015
DOI: 10.7314/apjcp.2015.16.15.6215
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Suppression Mechanisms of Protein Tyrosine Phosphatase O and Clinical Applications

Abstract: Tyrosine phosphorylation plays an important role in regulating human physiological and pathological processes. Functional stabilization of tyrosine phosphorylation largely contributes to the balanced, coordinated regulation of protein tyrosine kinases (PTKs) and protein tyrosine phosphatases (PTPs). Research has revealed PTPs play an important suppressive role in carcinogenesis and progression by reversing oncoprotein functions. Receptor-type protein tyrosine phosphatase O (PTPRO) as one member of the PTPs fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Reduced expression of this gene was also observed in B-cell chronic lymphocytic leukaemia (44). Moreover, the re-activation of PTPRO in tumour tissues can either contribute to tumour reduction or improve its susceptibility to chemotherapy (42,45). It is postulated that PTPRO regulates insulin and lipid metabolism via the PI3K/Akt/MDM4/MDM2/P53 pathway by influencing autophagy (46).…”
Section: Resultsmentioning
confidence: 99%
“…Reduced expression of this gene was also observed in B-cell chronic lymphocytic leukaemia (44). Moreover, the re-activation of PTPRO in tumour tissues can either contribute to tumour reduction or improve its susceptibility to chemotherapy (42,45). It is postulated that PTPRO regulates insulin and lipid metabolism via the PI3K/Akt/MDM4/MDM2/P53 pathway by influencing autophagy (46).…”
Section: Resultsmentioning
confidence: 99%
“…The previous results of this study showed that the expression level of PTPRO was positively correlated with the prognosis of various solid tumor and was also closely related to the clinical characteristics [12,22]. Therefore, we further explored whether PTPRO could be used to assess the prognosis of LUAD.…”
Section: Construction Of a Nomogram Based On Ptpro Expression Levelsmentioning
confidence: 93%
“…While numerous researchers focus on PTKs, which have dominated the cancer target therapeutics sphere. Increasing articles have reported that PTPs play a role in certain physiological and pathological activities by regulating tyrosine dephosphorylation, which is an opposing but equally significant mechanism as PTKs [3,4]. Protein tyrosine phosphatase receptor type O (PTPRO), one of the receptor-type PTPs (RPTPs), was first found in renal glomerular epithelial cells [5].…”
Section: Introductionmentioning
confidence: 99%